Review Thermal Management System of Battery for Electrical Vehicles - Sirikasemsuk, Sarawut; Naphon, Paisarn; Wiriyasart, Songkran (Srinakharinwirot University Engineering Journal, 2021)
At the present, batteries are essential energy storage for electrical vehicles. The efficiency and lifetime of the battery can be extended by keeping the working temperature about 15°C - 40°C. The generated heat inside the batteries can be generated by the charging, discharging, physical actions such as compression crushing or piercing from an accident including the electrical-chemical system problems of the battery. The thermal problem, the high temperature causes the battery overheating and explosion due to the thermal runaway phenomenon. Therefore, the thermal management systems are essential for cooling the battery system, and have been designed with different cooling techniques; air, liquid, and hybrid coolants. From the review process, it is found that the cooling technique with liquid as coolant gives the highest thermal efficiency. However, the operating temperatures obtained from three cooling techniques are less than 40oC. The cooling techniques can be used to design and apply for developing electric vehicle battery system with high lifetime and more safety too.